(untitled) - Kim, W. Chan (Boston, Massachusetts, 2015)
Blue Ocean Strategy presents a systematic approach to making the competition irrelevant and outlines principles and tools any organization can use to create and capture their own blue oceans
Keywords: Market segmentation,Sản phẩm mới,Sản phẩm mới,Phân chia thị trường,New products